Estimation of Municipal Income Distribution in Mexico - Mario Miguel Ojeda Ramírez; Roberto Gallardo Del Ángel; Cecilia Cruz López (Entreciencias: Diálogos en la Sociedad del Conocimiento)
Purpose: To ffer an estimation of income distribution measures for municipalities in Mexico for year 2015, and also an analysis of municipal grants on income inequality.